"A Catastrophe Happening in Front of Our Very Eyes": The Environmental History of a Comet Crash on Jupiter. (26th September 2016) - Degroot, Dagomar
Abstract : Earth is part of a vast cosmic environment, thus environmental history should embrace the whole universe. This article argues that changes in environments far removed from Earth have had profound consequences for human history. It explores complex intellectual, cultural, and political responses to the collision between Jupiter and the fragments of comet Shoemaker-Levy 9. In 1993 the discovery of the disintegrated comet was made possible by environmental changes in the vicinity of Jupiter, and by scientific, technological, and cultural developments that changed what astronomers looked for in the heavens. When scientists realized that the comet's remnants would collide with Jupiter, they set up an unprecedented observation program. The impacts of the cometary fragments in July 1994 altered scholarly understandings both of the solar system and of Earth's natural history. Millions of people followed the collisions not only in traditional media, but also online, in a breakthrough moment for the early internet. Others directly viewed the impacts through small telescopes and binoculars in ways that transformed how they understood the security of life on Earth. Political responses to the collisions intensified existing programs for detecting Earth-approaching objects, which made possible government and corporate initiatives aimed at exploiting the alien environments of those objects. By revealing the fragile nature of earthly environments, environmental changes in one part of the solar system may provoke humans to change environments in another.